Vector tugs actuation modeling for ship maneuvering simulators. - Barrera, Rodrigo Domingos (2019)
Ship Manoeuvring Simulators have proved to be powerful tools on analyzing the feasibility of new maritime maneuvers and new port constructions. In order to provide a complete immersive and real environment, such simulators must correctly represent the dynamics of the controlled vessel as well as the actuation of the tugboats, which have been extremely used over the last years due to the increasing complexity on the maritime maneuvers. Although few simulators can correctly model the dynamics of the tugboats, they still represent their actuation through the so-called \"vector tug model\". This is usually the case because it is expensive to run several integrated-simulators in real-time and the simulator centers do not have trained tugboat captains available. The vector tugs are usually represented as simplified external forces actuating on a vessel. The simplicity of such models causes a loss of realism during a maritime simulation due to the fact that neither the forces exerted on a towed vessel nor the tugboat\'s actuation position are accurate. In addition, tugboats\' actuation response time is usually not taken into account under the current vector tug models used on Ship Manoeuvring Simulators. The main objective of this work is to provide an innovative approach for vector tug actuation modeling in such a way that the towing force magnitude and actuation positions are accurate either in push or pull operation modes. The author will expand the static equilibrium model for tugboat force prediction presented in Brandner (1995) and Artyszuk (2014) and combine it along with optimization techniques in order to accurately obtain the tugboats\' actuation either working under the direct maneuver (i.e., tugboat uses solely its propeller power in order to exert force on a towed vessel) or working under the indirect maneuver (i.e., tugboats use the environmental disturbances and the hull drag in order to maximize their actuation force on a towed vessel). The implementation of the new mathematical model provides a new level of reality when vector tugs are used in Ship Manoeuvring Simulators.